Belonging in STEM: an interactive, iterative approach to create and maintain a diverse learning community. (November 2021) - Ayala, Marina J.; Carter, Javan K.; Fachon, Avani S.; Flaxman, Samuel M.; Gil, Michael A.; Kenny, Heather V.; Laubach, Zachary M.; Madden, Sage A.; McDermott, Molly T.; Medina-García, Angela; Safran, Rebecca J.; Scherner, Ellen; et al.
Abstract : Diversity is a key driver of scientific innovation, yet fields in science, technology, engineering, and mathematics (STEM) have struggled to retain diverse communities. Research suggests that fostering a sense of belonging is critical for retaining diversity. We propose an iterative process that aims to improve sense of belonging among laboratory (lab) members through self-reflection and community collective action.